Accuracy of Self-Assessment and Peer Assessment in Learning : A Systematic Literature Review - Sinaga, Yohana Dwi Kristiani; Arliani, Elly; Ngala, Januarius Clief; Agustina, Ni Luh Ika Tri (Jurnal Paedagogy, 2024)
This study aims to explore the influence of self-assessment and peer assessment in learning, the factors affecting the accuracy of self-assessment and peer assessment, and efforts to enhance the accuracy of self-assessment and peer assessment. This research was a qualitative approach with a systematic literature review method. The data collected are from national and international scholarly journals related to self-assessment and peer assessment in learning, which were then analyzed using content analysis. According to the study's findings, using peer and self-evaluation to evaluate students' learning had a very beneficial effect. Thus, it should be put into practice. Additionally, a number of factors, such as self-confidence, emotional intelligence, self-perception of abilities, prior experience, feedback quality, assessment instrument clarity, assessor agreement, and trust in peer assessment, affect how accurately learners assess themselves and each other. Clear assessment criteria and procedures, which provide students direction for both their own and their peers' evaluations, can increase the accuracy of peer and self assessments. Good feedback is essential to improving both assessment techniques' accuracy. In addition, sufficient instruction for pupils is required to guarantee that evaluations are more precise, impartial, and beneficial.